2021
DOI: 10.3389/fimmu.2021.648881
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Test Systems for the Detection of Antiphospholipid Antibodies in a Chinese Cohort

Abstract: BackgroundDiagnosis of antiphospholipid syndrome (APS) is based on the positivity of laboratory criteria antiphospholipid antibodies (aPLs). Test results for aPLs could be contradictory among different detection methods as well as commercial manufacturers. This study aimed to assess and compare the diagnostic and analytic performances of four commercial assays prevalently used in China.MethodsA total of 313 patients including 100 patients diagnosed with primary APS, 52 with APS secondary to SLE, 71 with SLE, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Another limitation might be related to the laboratory methods used to test the aPLs, as there are constant discussions over the need for the standardization of APS tests, and the last updated guidelines included a mixing test for LA detection [31]. Even so, the kits used in our laboratory of immunology were among the assays tested and recommended for the APS assessment [32,33]. We do not present data about the persistence of aPLs for more than 12 weeks.…”
Section: Discussionmentioning
confidence: 95%
“…Another limitation might be related to the laboratory methods used to test the aPLs, as there are constant discussions over the need for the standardization of APS tests, and the last updated guidelines included a mixing test for LA detection [31]. Even so, the kits used in our laboratory of immunology were among the assays tested and recommended for the APS assessment [32,33]. We do not present data about the persistence of aPLs for more than 12 weeks.…”
Section: Discussionmentioning
confidence: 95%
“…Complications leading to thrombophilia were also involved in the exclusion criteria, which might prevent some elderly patients from entering our cohort. In addition, differences in the age distribution pattern of APS between ethnic groups were suspected, since previous studies reported a younger APS population from East Asia than that from Europe ( 20 , 21 ). A larger study should be expected to investigate the role of age in the prognosis of ptAPS.…”
Section: Discussionmentioning
confidence: 99%
“…First, autoantibodies in patients with RA are heterogeneous, having different affinities, subtypes, and glycosylation patterns. Second, technical aspects of the assays varied, including cut-off values, methods of calibration and quantitation, choice of solid phase and coating, and type and source of antigen ( 23 ). Last, the performance of different detection methods may be influenced by antigen epitopes (linear epitopes, spatial conformation epitopes).…”
Section: Discussionmentioning
confidence: 99%